Teaching style and academic engagement in pre-service teachers during the COVID-19 lockdown: Mediation of motivational climate - López-García, Ginés D.; Carrasco-Poyatos, María; Burgueño, Rafael; Granero-Gallegos, Antonio (Frontiers in Psychology, 2022)
COVID-19 and the resulting confinement has had a great impact on the educational environment. Although research in initial teacher education has focused on studying the factors that lead to increased academic engagement, there is no evidence that examines the role of teacher interpersonal style and motivational classroom in a virtual learning context. The aim of this research was to analyse the mediating role of motivational climate between teacher interpersonal style (i.e., autonomy support and controlling style) and academic engagement climate in pre-service teachers in a resilient context. The research design was observational, descriptive, cross-sectional, and non-randomized. A total of 1410 university students (pre-service teachers) participated (Mage=23.85; SD=5.13) (59.6% female; 40.3% male; 0.1% other). The scales of interpersonal teaching style, classroom motivational climate, academic commitment, and resilience were used, and a structural equation analysis with latent variables was carried out controlling resilience and gender. The results of the structural equation model show the importance of student perception of teacher autonomy support on academic engagement of the pre-service teachers, as well as the mediation of the mastery climate between autonomy support and academic engagement. For this reason, in order to increase academic engagement in pre-service teachers, it is recommended the use of motivating styles and instructional strategies focused on supporting the decision-making process, initiative, and significant learning.